SISTEM REKOMENDASI DESTINASI WISATA DI KOTA KUPANG DENGAN METODE WEIGHTED PRODUCT - Overbeek, Marlinda Vasty; Naatonis, Remerta Noni (STIKOM Uyelindo Kupang, 2019)
From 2006 to the latest data collection in 2017, the number of domestic and foreign tourists visiting East Nusa Tenggara is increasing. In Kupang city as the provincial capital of East Nusa Tenggara. Kupang City is not just a temporary stop when tourists want to transit to other islands in East Nusa Tenggara but have become tourist destinations. The increasing number of tourist visits is not accompanied by a system of recommendations about tourist destinations in the city of Kupang, In this study a recommendation system was built in Kupang City using the weighted product method, which is one of the techniques of Multiple Alternative Decision Making. Weighted products use multiplication to connect attribute ratings. The criteria used in this study are 3 criteria, namely costs, facilities provided and reviews from previous visitors. While for locations or tourist destinations there are 55 tourist destinations in Kupang City which are the alternatives in this study. From the results of the study, for natural attractions, Namosain Beach ranked first to be visited with a value of 0.00519. As for artificial tourism objects, Nostalgia Park is the first place with a value of 0.0805. As for culinary tourism, Nostalgia Park culinary ranks first at 0.0904.